If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -2) = -4(5 + x) Reorder the terms: 3(-2 + x) = -4(5 + x) (-2 * 3 + x * 3) = -4(5 + x) (-6 + 3x) = -4(5 + x) -6 + 3x = (5 * -4 + x * -4) -6 + 3x = (-20 + -4x) Solving -6 + 3x = -20 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -6 + 3x + 4x = -20 + -4x + 4x Combine like terms: 3x + 4x = 7x -6 + 7x = -20 + -4x + 4x Combine like terms: -4x + 4x = 0 -6 + 7x = -20 + 0 -6 + 7x = -20 Add '6' to each side of the equation. -6 + 6 + 7x = -20 + 6 Combine like terms: -6 + 6 = 0 0 + 7x = -20 + 6 7x = -20 + 6 Combine like terms: -20 + 6 = -14 7x = -14 Divide each side by '7'. x = -2 Simplifying x = -2
| 8=-3p+5 | | 0=x^3-4x-48 | | 25z^2-10z=0 | | v^2+10v-21=0 | | 3(9-2)+9= | | s-9=10 | | 8x-3x=60 | | -j^2= | | j^2= | | 9x-28=5x | | 7a-6=15 | | 9n=8n+18 | | a+6a=98 | | -5*a=10 | | -8z-4=-4z | | -2(13x-6)+9(3x-3)-4=5-8 | | 3y+5y=64 | | 3a+6=9a+8 | | 6x^2-26x-20=0 | | 6x^2-26x+20=0 | | x^2=5-x | | -5=4t-13 | | -5*a=1o | | 6x^2+26x-20=0 | | 6x^2+26-20=0 | | d-(-0.8)=4 | | 9p-4p=30 | | 6*2j+2= | | 6*2j= | | -2(13-3)+9(3x-7)-6=5-9 | | 2*2j= | | 4x-3-8x+1=5x-9x+7 |